Promotion and Framework Act on Sport in South Korea and Japan : A Comparative Study - SangJin Yoon (Korea Institute of Sport Science, 2024)
PURPOSE This study aimed to explore the enactment and background of Korean and Japanese sports laws, comparatively analyze the major sports-related laws of both countries, namely Korean National Sports Promotion Act, Japanese Sport Promotion Act, and the Framework Act on Sport of both countries, and derive implications for the Korean Framework Act on Sport, sports-related laws, and sports policy. METHODS Research related to sports law were collected through academic databases and major search portals in both countries and analyzed. RESULTS First, as reviewed in previous studies, the Korean National Sports Promotion Act at the time of its enactment imitated the Japanese Sport Promotion Act in almost all articles. Second, Japanese Basic Act on sport, which was a complete revision of Japanese Sport Promotion Act, further expanded the concept of "sports," and specified nonexistent "sports rights," "sport nation," and "sport as a universally shared human culture," was evaluated as having quasi-constitutional character. Third, the Framework Act on Sport of both countries specified similar sports policies and concepts in many individual articles. The Korea's Framework Act on Sport independently included articles for superordinate law, spread of sports values into environmental and political fields, inter-Korean exchange and cooperation in sports, sports donation culture, and so on . Japan's Basic Act on Sport independently specified preamble, sports integrity-related articles, articles for prompt and appropriate resolution of sports disputes, and for promoting anti-doping activities, and so on. CONCLUSIONS This study offers suggestions for clarifying the legal concepts of "sports" and "physical education," resolving contradictions in the articles of the Korean Sports-related Act, establishing an independent sports policy implementation organization, establishing the legal system of the Korean Sports-related Act, and supporting the "life career" from the time of active athletes.